Respuesta :
First, distribute to simplify the equation.
-3*w = -3w
-3*4 = -12
-3w + (-12) = -18
Now, isolate the variable.
-3w + -12 = -18
+12 +12
- 18 + 12 --> -6
-3w = -6
-3w/-3 = -6/-3 >>>>> w = 2
Answer: w = 2
-3*w = -3w
-3*4 = -12
-3w + (-12) = -18
Now, isolate the variable.
-3w + -12 = -18
+12 +12
- 18 + 12 --> -6
-3w = -6
-3w/-3 = -6/-3 >>>>> w = 2
Answer: w = 2
-3(w+4) = -18
⇒ -3w -3*4= -18 (distributive property)
⇒ -3w -12= -18
⇒ -3w= -18+ 12
⇒ -3w= -6
⇒ w= -6/(-3)
⇒ w= 2
Final answer: w= 2~
⇒ -3w -3*4= -18 (distributive property)
⇒ -3w -12= -18
⇒ -3w= -18+ 12
⇒ -3w= -6
⇒ w= -6/(-3)
⇒ w= 2
Final answer: w= 2~